Trauma exposure, posttraumatic stress, and preventive health behaviours: a systematic review. Issue 1 (2nd January 2018) - Lee, Sharon Y.; Park, Crystal L.
ABSTRACT: Psychological trauma has implications for many aspects of physical health, including preventive health behaviours (PHBs). However, whether trauma exposure additionally contributes to PHBs above and beyond the effects of posttraumatic stress disorder (PTSD) symptoms remains unclear. In this systematic review, 32 studies were analysed to characterise: (1) the relationships between trauma exposure and PHBs, (2) the relationships between PTSD symptoms and PHBs, (3) the unique associations between trauma exposure and PHBs, independent of PTSD symptoms, and (4) the unique associations between PTSD symptoms and PHBs, independent of trauma exposure. Findings were variable across the three examined PHBs (physical activity, diet, medical screening) when only trauma exposure or PTSD symptoms were taken into account. Clearer relationships emerged between trauma exposure and PHBs when PTSD symptoms were taken into account, demonstrating that trauma exposure is related to PHB engagement above and beyond the effects of PTSD symptoms. Additionally, PTSD symptoms shared unique associations with physical activity and screening frequency, which were not explained by trauma exposure. Our review reveals that teasing apart the effects of trauma exposure and PTSD symptoms on PHBs brings greater clarity to the strength and direction of these associations.